The Trend of Plastic Recycling Policies in Japan on the Current Legal Regulation of Transboundary Movements of Plastic Waste - Yunhan Yang (Studies in Law and Justice, 2023)
Since China’s import ban on solid waste in 2017 and the entry into force of “Plastic Amendment” to the Basel Convention, global plastic waste trading has entered a new historical stage that transboundary movements of plastic waste is no longer regarded as a wise approach for many developed countries. Due to the fact that China, a traditional plastic-importing country, no longer accepts plastic waste after 2021, and the strict regulations on cross-border plastic transactions under the amendment to the Basel Convention, the circulation of plastic waste is increasingly restricted, making it imperative for the world to build a new plastic disposal system to deal with the immediate crisis. As a traditional plastic-export country in Asia, Japan faces domestic plastic overstocking crisis as well. However, as a well-known environmentally-friendly country, Japan’s new policies and legal perfection implemented thereafter have triggered concerns. Regulations through the whole process including production, use, recycling of plastic have clearly specified the responsibilities of main bodies, and the macro control of product production standards sets a unified supervision system at the national level. The valuable experience of this “Japanese Model” can provide some references for China’s future improvements of domestic plastic waste management.